Peran Teknologi Ufed Cellebrite Dalam Pengungkapan Kasus Narkotika Pada Bidang Laboratorium Forensik (BIDALABFOR) Polda Riau - Dinda Dwi Putri; Rio Tutrianto (UIR PRESS, 2025)
One of the roles of technology used in uncovering crime cases, especially drug crimes, is by utilizing technology called cellebrite UFED. Cellebrite UFED is software specifically designed for digital forensics professionals such as law enforcement, security agencies, and investigative companies. This software allows users to collect, analyze, and recover data contained in mobile devices such as smartphones, tablets, and computers. Using qualitative methods by conducting indepth interviews with sources. This research explains that Cellebrite's UFED can extract various types of data from mobile devices, including text messages, call logs, contacts, images, videos, and application data. This tool supports thousands of device models from various manufacturers and operating systems, including Android and iOS. This tool is designed to maintain data integrity during the extraction process, ensuring that digital evidence is not affected or altered. This is important to maintain the validity of evidence in a legal context in cases such as narcotics cases. In addition to data extraction, Cellebrite UFED provides analysis tools that help investigators identify and correlate patterns in extracted data. This feature is very useful in criminal investigations, such as narcotics crime suspects who use communication devices such as cellphones for transactions. With automation and advanced features, Cellebrite UFED increases efficiency and accuracy in the digital inspection process. This allows investigators to work faster and with fewer errors. Overall, Cellebrite UFED is a highly effective and important tool in the field of digital forensics, providing a comprehensive solution for the extraction, analysis and reporting of data from mobile devices.